Tanggung Jawab Notaris Dalam Memberikan Perlindungan Data Pribadi Para Pihak - Afrihani, Azhara; Yogantara S., Pande; Widiatedja, I Gusti Ngurah Parikesit (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 9 No 01 (2024), 2024)
The purpose of this research is to investigate the function of Notaries in securing personal data and the mechanism of legal protection , particularly if the Notary violate s his obligations . This research employs qualitative research and normative legal methods with a statutory approach and conseptual approach. The result finds that Notary profession has special authority in making authentic deeds and a profession that can keep the data remains confidential.  If the Notary violates his obligations, The Notary may face punishment under the UUJN, namely written warning, interim suspension, honourable dismissal, or dishonourable dismissal. According to the PDP Law, it can be applied as legal protection for a person in maintaining the security of personal data or the confidentiality of deeds they make if seen from the UUJN. In the PDP Law, the Notary is a legal subject who controls personal data Notaries are legal subjects who control personal data contained in authentic deeds and determines the objective of processing the personal data. Authentic deeds or personal data of interested parties are the responsibility of a Notary to safeguard them.